Internet Pornography Addiction and Adolescent Sexual Behavior: Is There Any Connection? - Ida Ayu Eka Adnyani; Asep Arifin Senjaya; Ni Wayan Aryani (Media Keperawatan Indonesia)
Addiction to pornographic content is a form of behavioral addiction that is characterized by a strong desire to access pornographic content for a long period of time and feel happy. The aim of this research is to determine the relationship between addiction to pornographic content on the internet and adolescent sexual behavior at the Yapparindo Klungkung Tourism Vocational School in 2024. The type of research is cross-sectional analysis with a sample of 39 students. Data collection uses a questionnaire. Univariate data analysis in the form of frequency distribution and bivariate using the Chi Square test with a significance level of p<0.05. The research results were that most of the students were 17 years old and male. Addiction to pornographic content is mostly mild, namely 30 respondents. Adolescent sexual behavior among students is mostly mild; as many as 22 respondents. The conclusion of the research is that there is a relationship between addiction to pornographic content on the internet and the sexual behavior of teenagers at Yapparindo Klungkung Vocational School. The advice given is that parents and teachers can deepen religious values and provide education on the importance of healthy dating, as well as improve communication with students.